P. Tillich‘s ontology and I. Kant‘s Transcendental Philosophy - Briedis, Mindaugas (Problemos, 2004)
This article seeks to examine to what extent Tillich’ s ontology draws on Kant’s critique of dialectical reason. It is shown that Kant’s refutation of the ontological proof of God means a departure from objective uncertainty towards practical certainty, while Tillich’s analysis of existence allows for truth to be regarded as being both personal and objective. For Tillich, an openness to the transcendent had to be found in the human ontological structure itself as an existing individual, a self. The existential category of finite subjectivity can be said to be correlate of both the instant and existence itself. Kant’s transcendental philosophy begins with an attempt to solve the theoretical problem of the possibility of synthetic a priori judgments. In solving this epistemological problem Kant demonstrates how transcendental knowledge (i.e., knowledge of the synthetic a priori conditions for the possibility of experience) is possible only when its application is confined to the realm of empirical knowledge (i.e., to experience). He argues that space, time, and the twelve categories form the transcendental boundary line between what we can and cannot know. But this “solution” itself calls attention to an even more significant problem: what is the status of that which lies outside the boundary of possible empirical knowledge? According to Kant our ideas of God, freedom, and immortality inevitably arise in the human mind as a result of our attempts to unify and systematize our empirical knowledge. In other words, reason naturally seeks for something beyond the limits of empirical knowledge which can supply unity and coherence to the diversity of facts which fall within that boundary. Kant’s moral argument for God’s existence assumes that the moral law exists and that it can be fulfilled only by the retributive justice of an omnipotent God. Though Tillich agrees with Kant that faith being of an existential character involving the whole of human existence, does not constitute a theoretical problem of the sort we encounter in empirical inquiry, but because of this wholeness Tillich sees Kant’s moral solution concerning nature of religion as reductive and suggests that an act of faith is a matter of all mental functions (intellect, will, emotion) of human being.